Malignant Mesothelioma in Cappadocia: Data from Eight Regional Hospitals - İpek Pınar Aral; Mehmet Beşiroğlu; Süheyla Aytaç Arslan (İstanbul Medical Journal, 2020)

(untitled)
Introduction:This study aimed to describe the current situation of malignant mesothelioma (MM) by examining data from 8 state hospitals in Cappadocia, where one of the most serious mesothelioma endemics is observed. Recently, no assessment of this endemic has been conducted in Cappadocia. Therefore, this study aimed to provide up-to-date information regarding the current situation.Methods:Patients with pleural or peritoneal MM admitted to local state hospitals in Cappadoccia between 01.01.2007 and 25.09.2019 were retrospectively evaluated. The primary endpoint of the study was the overall survival (OS). The secondary endpoint was the evaluation of the current status of MM cases in Cappadocia and the determination of patients’ access to health care.Results:Seventy-one patients were retrospectively evaluated. The median follow-up period was 26 months (range: 1-153); 55 patients (77.5%) died, while 16 patients (22.5%) survived. Sixtysix (93%) patients were diagnosed with pleural MM and 5 (7%) patients were diagnosed with peritoneal MM. It was observed that 18 (25.4%) of the patients resided in Sarıhıdır, Karain and Tuzköy, which was the decision to evacuate. Median OS was 16 months (range: 1-133) for pleural MM and 21 months (range: 9-117) for peritoneal MM. Significantly higher OS was observed in patients aged 60 years or less at the time of diagnosis (p=0.014). Only 6 patients (8.5%) were diagnosed at Nevşehir Hospital and 91.5% of 65 patients were diagnosed outside the Cappadoccia.Conclusion:The current situation of MM in Cappadocia was evaluated in this study. The OS of MM patients has not changed dramatically in the last 30 years. Approximately 90% of patients had to move out of the province for diagnosis and treatment. Further studies are needed to evaluate the current situation and treatment outcomes in this region.